Synthesis, Cytotoxicity Study, And Molecular Docking Of New Imidazole-Based Chalcone And Pyrazoline Hybrids - Bakar, Bazri Izwan (2023)
Cancer is one of the leading diseases across the globe, and breast cancer has become the most common disease among women. There is an ongoing search for a new chemotherapeutic agent to control this condition due to the limitations of existing anticancer drugs, such as the adverse effects and drug resistance. Compounds that consist of scaffolds from natural products such as chalcone and pyrazoline have shown diverse pharmacological activity, particularly as an anticancer agent. Hybrid compounds consisting of more than one active pharmacophore have proven to target various mechanisms of action. In this study, hybrid imidazole-chalcones, 1–3 were synthesised via a Claisen-Schmidt condensation reaction. The cyclisation of these compounds formed imidazole-pyrazoline derivatives, 1-3 (i-iii). Fourier Transform Infrared (FTIR) and Nuclear Magnetic Resonance (NMR) spectroscopies were utilised to characterise all these compounds. The molecular docking of these compounds (ligands) with estrogen receptor alpha protein (3ERT) was performed using AutoDock 4.2 software to investigate their interactions. Further in silico study using SwissADME web tools was performed to analyse their physicochemical and pharmacokinetic properties and drug-likeness properties. The in vitro cytotoxicity activity was assessed by utilising an MTT assay against the breast cancer cell line, MCF-7 with Tamoxifen as a positive control. The result emphasised that all compounds did not show significant inhibitory action.